Effect of aerial spray adjuvant applying on the efficiency of small unmanned aerial vehicle for wheat aphids control - Meng, Yanhua; Lan, Yubin; Mei, Guiying; Guo, Yongwang; Song, Jianli; Wang, Zhiguo (International Journal of Agricultural and Biological Engineering, 2018)
Small unmanned aerial vehicles (UAVs) have been widely used in different aspects of modern farming management, including pest and disease control in China in recent years. In this study, the spray performance of a small plant protection UAV at low volume spray was evaluated by adjusting the pesticide dosage and adding aerial spraying adjuvants. Droplet deposition, droplet density, coverage, control effect and pesticide residue from field trials were assessed. In addition, the residue and control effect of UAV spray were compared to manual knapsack at high volume spray. The results showed that, the adjuvant applying improved the efficiency of UAV spray. Also, the adjuvant applying reduced the dosage of imidacloprid by 20%. However, there was no significant difference on initial residue between UAV spray and knapsack spray. Thus, plant protection UAV spraying pesticide by adding appropriate adjuvant showed the ability of improving the pesticide effectiveness by improving the control efficiency, reducing the pesticide dosage and residue. Keywords: unmanned aerial vehicle (UAV), aerial spraying adjuvant, deposition, control efficiency, pesticide residue, wheat aphid DOI: 10.25165/j.ijabe.20181105.4298 Citation: Meng Y H, Lan Y B, Mei G Y, Guo Y W, Song J L, Wang Z G. Effect of aerial spray adjuvant applying on the efficiency of small unmanned aerial vehicle on wheat aphids control. Int J Agric & Biol Eng, 2018; 11(5): 46–53.